2018
DOI: 10.4103/jmau.jmau_25_18
|View full text |Cite
|
Sign up to set email alerts
|

Histological effects of gold nanoparticles on the lung tissue of adult male albino rats

Abstract: Short Introduction:Nanoparticles (NPs) represent a new line in the investigations and treatment of group of diseases. Furthermore, it is found in many products and enters the body by different roots as ingestion and inhalation. Lung is more liable to exposure to these particles. Safety of these particles on the lung needs to be examined.Aim of the Work:To study the effect of gold NPs (GNPs) on the histological structure of the lung tissue.Materials and Methods:Thirty-six healthy male albino rats were randomly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
1
12
1
Order By: Relevance
“…the ingestion by licking of particles that accumulate on the skin and the fur. In this context, it is interesting to note that, in a study on the effect of orally administered 10-20 nm AuNPs on the histological structure of the rat lung tissue, pulmonary damage was observed (Elbakary et al 2018). In this research, adult male albino rats were divided into three groups: two groups treated with AuNPs (one receiving a low dose and another one receiving a high dose every day) and a control group.…”
Section: Sung Et Al (2011)mentioning
confidence: 98%
See 1 more Smart Citation
“…the ingestion by licking of particles that accumulate on the skin and the fur. In this context, it is interesting to note that, in a study on the effect of orally administered 10-20 nm AuNPs on the histological structure of the rat lung tissue, pulmonary damage was observed (Elbakary et al 2018). In this research, adult male albino rats were divided into three groups: two groups treated with AuNPs (one receiving a low dose and another one receiving a high dose every day) and a control group.…”
Section: Sung Et Al (2011)mentioning
confidence: 98%
“…On the other hand, the whole-body inhalation system involves other types of exposure such as, in particular, ingestion. As it has been shown that oral administration can cause lung damage (Elbakary et al 2018), also the exposure by whole-body inhalation chamber is not ideal as it may lead to an overestimation of the damage. The main limitations of in vivo studies are therefore due to the lack of an appropriate model of exposure.…”
Section: Sung Et Al (2011)mentioning
confidence: 99%
“…Although the excretion route of the gold nanomaterials will also depend on their size and shape, there is some agreement that the use of particles between 10 and 100 nm slows down the activation of the mononuclear phagocyte system, while still being large enough to avoid immediate renal filtration [44][45][46]. It should be noted that in contrast with the study of Elbakary et al [27], these investigations indicate very little or no toxicity, reflecting the more realistic doses employed.…”
Section: Toxicology and Organ Distributionmentioning
confidence: 84%
“…However, there is a degree of consensus regarding the role of positive surface charge in the induction of ROS and pro-inflammatory mediators [ 26 ]. A study by Elbakary et al [ 27 ] indicated the occurrence of lung remodelling after intratracheal instillation of gold nanoparticles in healthy adult male rats, exhibiting congestion of blood vessels, alveolar collapse, extravasation of red blood cells and thickening in the alveolar wall, suggesting fibrosis. However, the rats were exposed to 40 or 400 µg/kg of the nanomaterial every day for 14 days — doses which might be expected to induce pulmonary inflammation independent of any innate particle toxicity.…”
Section: Lc and Gold Nanomaterialsmentioning
confidence: 99%
“…From this point, gold is the most suitable metal for nanotechnology. One of the most affected organs for local and systemic drug delivery is the lung because of its large surface area and close contact with the blood circulation [3]. A comparative evaluation of the biodistribution and the toxic profiles of GNPs and SilverNano Particles (SNPs) showed that their chemical composition played a critical role in their in vivo biodistribution and toxicity.…”
Section: Introductionmentioning
confidence: 99%